A deep insight into mechanism for inclusion of 2R, 3R-dihydromyricetin with cyclodextrins and the effect of complexation on antioxidant and lipid-lowering activities. (June 2020) - Wu, Yanping; Xiao, Yue; Yue, Yuxi; Zhong, Kai; Zhao, Yinglan; Gao, Hong
Abstract: 2R, 3R -Dihydromyricetin (DMY) is a natural flavonoid that has versatile biological activities. However, due to its poor water solubility and low chemical stability, its applications in food and pharmaceutical fields remain limited. Inclusion of DMY with cyclodextrins (CDs) has been shown to improve the solubility and stability of DMY, whereas the mechanism for the inclusion has not been elucidated. This study investigated the characteristic and mechanism for inclusion of DMY with CDs, and evaluated the effects of complexation on antioxidant and lipid-lowering activities of DMY. Phase solubility studies revealed that the solubility of DMY was significantly improved in the presence of natural (α-, β-, γ-) CDs and their derivatives, namely hydroxypropyl-β-cyclodextrin (HP-β-CD) and (2, 6-di-O-methyl)-β-cyclodextrin (DM-β-CD), by forming 1:1 stoichiometric inclusion complexes. Particularly, the complexes of DMY with HP-β-CD and DM-β-CD were prepared and characterized by FT-IR, PXRD, DSC, SEM and NMR analysis. Furthermore, the possible inclusion configuration was verified by molecular docking, which indicated that B-ring of DMY was fully embedded in the cavity of CDs while C-ring and A-ring were partly included, through non-covalent interaction such as hydrogen bonding. The results also showed that inclusion of DMY with HP-β-CD or DM-β-CD enhanced the radical scavenging capacity of DMY and maintained its lipid-lowering effect in hyperlipidemia zebrafish model. Graphical abstract: Image 1 Highlights: The inclusion mechanism of DMY with cyclodextrins has been elucidated. The B-ring of DMY was fully embedded in cyclodextrins cavities. The antioxidant and lipid-lowering activities of DMY were improved after complexation. Inclusion DMY with cyclodextrins is useful to broaden its application.